Cardiac changes in asphyxiated neonates-need for early detection to improve long-term outcome - Lakshmanan, Raja; Verma, Yogendra Singh (International Journal of Contemporary Pediatrics, 2017)
Background: Cardiac changes are common in Perinatal asphyxia. Detecting them early will help in specific management and good long-term outcome. Cardiac monitoring is recommended in every resuscitation as per NRP 7. Objective of present study was to evaluate myocardial dysfunction in neonates having Hypoxic Ischemic Encephalopathy by clinical, electrocardiographic and echocardiographic examination. Methods: Observational analytical study of 79 neonates who suffered from asphyxia as per selection criteria were done at medical college hospital. Myocardial dysfunction was evaluated by clinical features assessed on first 2 days and electrocardiographic and echocardiographic examination was done after 24 hours. Data were collected and analysed by SPSS 21 software. Results: Respiratory distress was found in 67.08% of the subjects. Prolonged capillary refill time was found in 39.24% of the subjects. Mean QTc (ms) interval was prolonged in non-survivors (496.6±20.8) when compared with survivors (418.2±33.7) (p - 0.000). T wave changes were present in non-survivors (94.7%) when compared to survivors (41.7%) (LR- 19.558). ST wave changes were present in non-survivors (73.7 %) compared with survivors (10%) (LR- 28.483). Mean Ejection Fraction (%) was shortened in non-survivors (53.79±7.53) compared with survivors (71.48±10.28) (p-0.000). Significant tricuspid regurgitation (78.94%) was present among non-survivors compared to survivors (10%) (LR- 17.859). Evidences of significant pulmonary artery hypertension were found in most of the (78.94%) non-survivors compared to survivors (10%) (LR-22.4). Similarly, severe grades of asphyxia had significantly high findings of increased CRT, reduced EF, LVES, ST and T wave changes etc. Conclusions: Cardiac changes in severe asphyxia are high and can be identified early by clinical, electroctrocardiographic and echocardiographic examination.